2018
DOI: 10.1096/fj.201701139r
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic PHD2/HIF‐1α axis is involved in postexercise systemic energy homeostasis

Abstract: Exercise plays an important role in the prevention and treatment of chronic liver disease and associated metabolic disorders. A single bout of exercise induces tissue blood flow redistribution, which decreases splanchnic circulation and leads to physiologic hypoxia in the gastrointestinal system and liver. The transcription factor, hypoxia inducible factor-1α (HIF-1α), and its regulator, prolylhydroxylase 2 (PHD2), play pivotal roles in the response to oxygen flux by regulating downstream gene expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…VHL deletion in hepatocytes, which is preventing the proteasome degradation of HIFα subunits, resulted in the overexpression of both HIF1α and HIF2α and then in the rapid development of an impressive fatty liver associated with an impairment of fatty acid oxidation [ 104 ]. Almost homologous results were obtained in other studies employing mice carrying hepatocyte conditional deletion of genes encoding for either PHD2 or PHD3 [ 105 , 106 ]. It should be noted, however, that fatty liver developed in all these transgenic mice in the absence of any induction of liver injury or metabolic alteration, and substantially so in an oxygen-independent way.…”
Section: Hif1α and Hif2α: Two Distinct Critical Players In Fibrogenic Cld Progressionsupporting
confidence: 76%
“…VHL deletion in hepatocytes, which is preventing the proteasome degradation of HIFα subunits, resulted in the overexpression of both HIF1α and HIF2α and then in the rapid development of an impressive fatty liver associated with an impairment of fatty acid oxidation [ 104 ]. Almost homologous results were obtained in other studies employing mice carrying hepatocyte conditional deletion of genes encoding for either PHD2 or PHD3 [ 105 , 106 ]. It should be noted, however, that fatty liver developed in all these transgenic mice in the absence of any induction of liver injury or metabolic alteration, and substantially so in an oxygen-independent way.…”
Section: Hif1α and Hif2α: Two Distinct Critical Players In Fibrogenic Cld Progressionsupporting
confidence: 76%
“…2, C–F). To detect which changes occurred in the gene expression level in the embryonic brain leading to the abnormal development during maternal cold stress, according to the previous studies, the indicated genes clusters were tested, including genes associated with low temperature sensitivity (RBM3 [Danno et al, 1997, Cirbp [Nishiyama et al, 1997], trpm8 [Palkar et al, 2018], and trpa1 [Moore et al, 2018]), metabolic sensitivity (HIF1a [Luo et al, 2018] and Ucp1 and Ucp2 [Margaryan et al, 2017]), and high temperature sensitivity (trpm2, trpv1, and trpv3 [Tan and McNaughton, 2016]; Fig. 2 G).…”
Section: Resultsmentioning
confidence: 99%
“…Early evidence for a role of HIFs in metabolic diseases was provided by hepatocyte-specific disruption of VHL 63 , PHD2 (REF. 64 ) or PHD3 (REF. 65 ), which triggered the O 2 -independent overexpression of both HIF1α and HIF2α and induced hepatic steatosis.…”
Section: Hypoxia and Hif1α In Metabolic Diseasesmentioning
confidence: 99%